MINAT SISWA KELAS X TERHADAP OLAHRAGA BASKET DI SMA NEGERI 10 KOTA JAMBI - Yogi Novriyanto Lumbanbatu; Sukendro; Bangkit Yudho Prabowo (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to explore and describe the interest of 10th-grade students in basketball at SMA Negeri 10 Kota Jambi. Student interest in this sport is viewed as a psychological attraction or passion for an object, which plays a significant role in future decision-making. The research method used is descriptive quantitative with a sample of 60 students randomly selected from a population of 120 10th-grade students. The data collection instrument is a questionnaire, which is analyzed using descriptive percentage analysis. The results of the study indicate that the majority of students have a very high interest in basketball, with 70% of students in the very good category and 30% in the good category. Factors affecting student interest include limited training time and parental support that prioritizes academic activities.